I, the Poet : First-Person Form in Horace, Catullus, and Propertius - McCarthy, Kathleen, 1962- (Book collections on Project MUSE., 2019)
"First-person poetry is a familiar genre in Latin literature. Building on the Greek poetic tradition of performed poetry, Latin poets such as Propertius, Catullus, Horace, and Ovid positioned their speakers both as participants in the poem's narrative and as narrators standing outside the poem and shaping its discourse. This book offers a model for understanding the ubiquitous use of a first-person voice in Latin poetry, taking on several of the central debates in the field of Latin literary studies-- including the inheritance of the Greek tradition, the shift from oral performance to written collections, and the status of the poetic "I-voice"--Through close readings of Catullus, Propertius, Horace, and (in the epilogue) Ovid. Moving beyond debates about how closely the textual speaker replicates the historical author, McCarthy analyzes poetic structure, showing how the poet draws the reader in by narrating scenes of address from which the reader is, paradoxically excluded, as if leaning in to listen to an overheard conversation"--